Thymomas - de los Santos, Julio (Cirugía del Uruguay, 1974)
The thymus is ongma embryologically as a symmetrical paired organ derived from the epithelium endodermal of the third branchial cleft. This origin is similar to that of the parathyroids inferiors, which are located posteriorly in the lower pole of the thyroid gland.